Theorem. The set $\{ x, \{ x, y \} \}$ obeys the property $$\underbrace{\{ x, \{ x, y \} \} = \{ x', \{ x', y' \} \}}_{(i)} \leftrightarrow (x = x') \wedge (y = y').$$
Proof.

Two sets are equal iff every element of one set is in the other set and vice versa. The proposition (i) is therefore equivalent to $$(\forall z) \: \underbrace{z \in \{ x, \{ x, y \} \} \leftrightarrow z \in \{ x', \{ x', y' \} \}}_{(ii)}.$$ The axiom of pair set requires that $$z \in \{ x, \{ x, y \} \} \leftrightarrow z = x \vee z = \{ x, y \}.$$ Now suppose $z = x \wedge z = \{ x, y \}$. According to the (axiomatic) symmetric and transitive property of the equation relation we get $x = \{ x, y \}.$ But this requires that there is an element in $x$ which is $x$. This contradicts the axiom of regularity: $$\neg ( x = \{ x, y \} \rightarrow x \in x ) \leftrightarrow ( x \notin x \rightarrow x \neq \{ x, y \} ).$$ From this it follows that either $z = x$ or $z = \{x, y\}$, but not both. A listing of all required implications is given as follows (it's a conjunction since (ii) has to hold for all z): $$(z = x \rightarrow z = x' \vee z = \{ x', y' \} ) \wedge (z = \{ x, y \} \rightarrow z = x' \vee z = \{ x', y' \}) \wedge (z = x' \rightarrow z = x \vee z = \{ x, y \} ) \wedge (z = \{ x', y' \} \rightarrow z = x \vee z = \{ x, y \}).$$ Assuming $(z = x \rightarrow z = \{ x', y' \}) \wedge (z = \{ x', y' \} \rightarrow z = \{ x, y \})$, the transitive property of implication has it that $z = x \rightarrow z = \{ x, y \}$ which is equivalent to saying that $x = \{ x, y \}$. Which is false due to the axiom of regularity (see above).

Going through all the possible permutations we find that the only valid implications are $$(z = x \rightarrow z = x') \wedge (z = \{ x, y \} \rightarrow z = \{ x', y' \}).$$ Or, equivalently, $$(x = x') \wedge (y = y').$$
2015 FEB 08 (v1.0)
Contact me: m.herrmann followed by an -at- followed by blaetterundsterne.org.

This document created with the help of MathJax (Thank you guys!)